2015
DOI: 10.3892/ol.2015.3821
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory neuroblastoma: A case report

Abstract: Abstract. Olfactory neuroblastoma (ON) is a rare type of malignant neoplasm originating from the olfactory neuroepithelial cells of the nasal cavity. ON is also known as esthesioneuroblastoma or neuroendocrine carcinoma. The malignancy accounts for <3% of tumors originating in the nasal cavity. Through the nasal cavity, ON may infiltrate the sinuses, the orbit and the cranium. The tumor is characterized by a pattern of slow growth and local recurrences. Treatment options are surgical excision or surgery combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Multimodality therapy, including chemotherapy, has been suggested by a number of studies (13)(14)(15)(16). In addition, recent study by Uslu et al (17) reported the case of a 69-year-old patient with olfactory neuroblastoma who was treated by combined surgical excision and radiotherapy. Currently, treatment with radionuclides bound to somatostatin analogues is performed in selected patients with neuroendocrine tumors, with considerable response.…”
Section: Introductionmentioning
confidence: 98%
“…Multimodality therapy, including chemotherapy, has been suggested by a number of studies (13)(14)(15)(16). In addition, recent study by Uslu et al (17) reported the case of a 69-year-old patient with olfactory neuroblastoma who was treated by combined surgical excision and radiotherapy. Currently, treatment with radionuclides bound to somatostatin analogues is performed in selected patients with neuroendocrine tumors, with considerable response.…”
Section: Introductionmentioning
confidence: 98%
“…[6][7][8][9] A nasal mass was often identified on nasoendoscopic examination in patients who presented with olfactory neuroblastoma. 6,[10][11][12][13][14] Olfactory neuroblastomas also have a bimodal age distribution, peaking in the second and sixth decades of life. 4 Our study population age has a mode in the fifth decade, which does not coincide with this bimodal age distribution.…”
Section: Discussionmentioning
confidence: 99%
“…ONB may histologically mimic a number of types of tumor within the sinonasal tract, making it much difficult to diagnosis [ 5 ]. Multi-modality imaging is essential to correctly assess the extent of the disease in the management of this infrequent tumor [ 6 ].…”
Section: Discussionmentioning
confidence: 99%